Analysis of Determinants of Factors Related to the Performance of Non-Communicable Diseases Development Post Cadres in Kendari City: Cross Sectional Study - Saida; Rahmawati; Wa Ode Syahrani Hajri (OPI Napoli, 2022)
Introduction: Non-communicable diseases (NCDs) are diseases that are not caused by bacterial infection and are the main cause of death in the world. The increase in NCDs cases also occurred in Southeast Sulawesi Province (Indonesia), including Kendari City. The purpose of this study was to analyze the determinants of proxies related to the performance of Integrated Non-Communicable Diseases Development Post (INCDDP) cadres in Kendari City, Indonesia. Materials and Methods: A cross-sectional study carried out in Kendari City, Southeast Sulawesi Province (Indonesia), with a population of all INCDDP cadres in the working area of PHC Abeli, Lepo-Lepo, and Perumnas. The sample consisted of 56 responders. Data were analyzed univariate and bivariate statistics, using the chi-square test. Multivariate using logistic regression. Results: The results of the research on the performance of INCDDP cadres were awards (p = 0.079), cadre training history (p = 0.031), infrastructure (p = 1.0) and knowledge (p = 0.007). The factor most related to the performance of INCDDP cadres was cadre knowledge (p = 0.019) with the coefficient of determination (R2) = 27.4%. Conclusion: Cadre performance is related to awards, cadre training history, infrastructure and cadre knowledge. The most related factor to INCDDP cadre performance is cadre knowledge.